Bamboo-flour-filled cost-effective poly(ε-caprolactone) biocomposites: a potential contender for flexible cryo-packaging applications. Issue 1 (19th November 2020) - Bhagabati, Purabi; Das, Deepshikha; Katiyar, Vimal
Abstract : Improvement of the physico-mechanical properties in melt mixed bamboo-root flour reinforced biodegradable poly(ε-caprolactone) biocomposites is demonstrated, aimed at flexible cryo-packaging applications. Abstract : Polymer-based packaging waste has caused increasing environmental concern, primarily owing to its non-biodegradable characteristics. Different grades of polyethylene (PE) dominate the entire world market as major flexible packaging materials, and one of the greatest reasons is their mechanical performance under cryogenic conditions. The current situation strongly demands biodegradable packaging materials, as an alternative to conventional non-biodegradable polymers, that meet all the conditions necessary to tackle environmental pollution. Poly(ε-caprolactone) (PCL) is a hydrophobic, fossil-fuel-based biodegradable polymer that has good mechanical properties under cryogenic conditions, making it a potential rival candidate to polyethylene for flexible cryo-packaging applications. However, the development of biodegradable cryo-packaging flexible materials with comparable mechanical performance and cost advantages compared to conventional ones is still a challenge. In the present research work, the issues of high cost and the relatively inferior mechanical performance of neat PCL have been dealt with by utilizing bamboo-root flour as a cost-effective, biobased reinforcing biofiller in the PCL polymer matrix. The reinforcing behaviour of the bamboo-root flour in the PCL matrix is revealed by the increased ultimate tensile strength (UTS) and tensile toughness values of PCL5, 29% and 56%, respectively, over neat PCL. The existence of polymer–filler interactions can also be inferred from the existence of the nanofibrillar morphology and the strong nucleation and trans-crystallization phenomena that are initiated at the surface of the biofillers, as evidenced by the results from scanning electron microscopy and polarized optical microscopy images. As part of the interesting observations in the system, the PCL biocomposite, with a maximum biofiller loading (30 wt%), has shown UTS (12.4 MPa) and % elongation at break (% EB, 243%) values close to those of linear low density polyethylene (LLDPE) (UTS: ∼12.6 MPa, % EB: ∼418%). The retention of the glass transition temperature ( T g ) of the PCL biocomposite filled with 30 wt% bamboo-root biofiller make it an optimum choice for flexible cryo-packaging applications.